Advances in water management under climate change - Mukesh Kumar; Kumar, Rohitashw (CRC Press, Taylor & Francis Group, 2024)
"Due to increasing population, decreased cultivable land, and mounting scarcity of water, it is essential to optimize the use of available resources. Climate change is occurring across the world but its effect may be local or region-specific, including localized watershed management. In order to minimize these effects, governments and environmental agencies encourage the adoption of "climate-smart" agricultural technologies, which involve implementing plans, programs, and projects to sustain and enhance watersheds. Advances in Water Management Under Climate Change examines all of these issues and provides best practices for sustainability"--